Pedagogical training and support requirements for effective facilitation of online course instructors - Cosmas Maphosa; Sithulisiwe Bhebhe (International Journal of Educational Management and Development Studies)
The Fourth Industrial Revolution (4IR), coupled with the COVID-19 pandemic and the resultant restrictions on social gatherings, saw many institutions of higher education transition from traditional face-to-face to online instruction. The transition was forced in response to a pandemic, and there were and still are numerous teething problems with effective online facilitation of learning. This desktop review paper discusses the pedagogical support requirements for course instructors for effective online learning facilitation. The findings of the study reveal that online teaching differs from traditional face-to-face learning due to geographical and physical distances. Instructors must understand and equip themselves with necessary knowledge and skills for effective online delivery. The discussion is premised on the view that effective online facilitation of learning should be based on sound pedagogical principles that bring to the fore the interplay between technology, content and pedagogy. The paper recommends deliberate and sustained training opportunities for online course instructors in all facets of online teaching and learning.